2015
DOI: 10.1200/jco.2015.33.3_suppl.252
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication of peritoneal cytology in the pancreatic cancer patients who underwent curative resection followed by adjuvant gemcitabine or s-1 chemotherapy.

Abstract: 252 Background: The clinical implications of peritoneal lavage cytology (CY) status in the patients who received curative resection and adjuvant chemotherapy have not been established. The clinical implications of peritoneal lavage cytology (CY) status in the patients who received curative resection and adjuvant chemotherapy have not been established. Methods: We retrospectively analyzed clinical data from 143 consecutive patients who underwent macroscopically curative resection and received adjuvant gemcitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Two studies did not perform a statistical analysis on OS and therefore no conclusions could be drawn, but one study possibly shows a possible trend towards a better OS in patients without OPTC (24 months in CY− patients vs. 15 months in CY+ patients) . In the other study the OS was 15 months in CY− patients versus 16 months in CY+ patients .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Two studies did not perform a statistical analysis on OS and therefore no conclusions could be drawn, but one study possibly shows a possible trend towards a better OS in patients without OPTC (24 months in CY− patients vs. 15 months in CY+ patients) . In the other study the OS was 15 months in CY− patients versus 16 months in CY+ patients .…”
Section: Resultsmentioning
confidence: 98%
“…Risk factor analysis demonstrated positive cytology to be an independent risk factor for a worse OS (Table ) . Other risk factors for a worse OS were lymphatic invasion , large tumor size , lymh node metastases, distant metastases, advanced stage (IIB or III), advanced tumor histological grade (G3) , portal vein invasion , invasion of the retroperitoneal tissue , vascular invasion , bile duct invasion , plexus invasion , positive resection margin , and recurrence site (worse OS in peritoneal recurrence vs. extraperitoneal recurrence) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some surgeons from Japan believed that CY+ status in the absence of other distant metastasis was not a contraindication for radical surgery and that surgical resection offered a chance for long-term survival [15, 16, 20, 25]. In contrast, other studies suggested that patients with CY+ experienced peritoneal recurrence and poor survival time inspite of radical surgery and adjuvant chemotherapy [1114]. In a recent large-scale multicenter study with 984 cases receiving R0 resection, Satoi and colleagues reported that OS of CY+ patients (median survival time: 16 months; 3 year OS rate: 6 %) was worse than CY− patients (median survival time: 25 months; 3-year OS rate: 37 %; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies from Japan reported that CY+ without distant metastasis should not preclude resection in resectable pancreatic cancer patients and that long-term survival was possible after adjuvant chemotherapy [15, 16, 20]. In contrast, several other studies showed that patients with CY+ status were associated with advanced disease and poor prognosis and had survival rates equivalent to other stage IV diseases [1114]. Due to these inconsistent conclusions, the American Joint Committee on Cancer and treatment guideline from the National Comprehensive Cancer Network considered CY+ as stage IV metastasis and contraindicator for pancreatic resection [21, 22].…”
Section: Introductionmentioning
confidence: 99%